The transformation of contemporary health care the market, the laboratory, and the forum - Moreira, Tiago (Routledge studies in health and social welfare, 2012)
"The past three decades have seen enormous changes in the organisation of health care. This book explores the role of knowledge production and technology on these transformations, focusing on the market (attempts to embed principles of economic rationality and efficient use of resources in the shaping and delivery of health care), the laboratory (science, experiments and 'evidence' in the management of research, practice and policy) and the forum (the application of deliberative procedures and other forms of public consultation to health care decision making)"--Provided by publisher.